2021
DOI: 10.3390/antiox10071131
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Motility, Oxidative Status, and Mitochondrial Activity: Exploring Correlation in Different Species

Abstract: Sperm quality assessment is the first step for evaluating male fertility and includes the estimation of sperm concentration, motility, and morphology. Nevertheless, other parameters can be assessed providing additional information on the male reproductive potential. This study aimed to evaluate and correlate the oxidative status, mitochondrial functionality, and motility in spermatozoa of two marine invertebrate (Ciona robusta and Mytilus galloprovincialis) and one mammalian (Bos taurus) species. By combining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Another explanation could be that Proline catabolism captures energy for the cells under nutrient depletion conditions, thereby protecting mitochondrial function (Tanner, 2019). The energy status and motility of spermatozoa are linked to mitochondrial activity (Bulkeley et al, 2021; Gallo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation could be that Proline catabolism captures energy for the cells under nutrient depletion conditions, thereby protecting mitochondrial function (Tanner, 2019). The energy status and motility of spermatozoa are linked to mitochondrial activity (Bulkeley et al, 2021; Gallo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] The mechanism of MSG as an Antioxidants can increase the motility of spermatozoa that have been exposed to oxidants. [17][18][19] Consuming MSG continuously at excessive doses can increase levels of free radicals that can cause oxidative stress. Physiologically, ROS is produced during the spermatogenesis process, but its presence must be neutralized with antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Mayer and Bukau [25] showed that the hydrolysis of ATP is significant for the protein chaperone HSP70. The sperm motility and complex mitochondrial respiratory activity are positively correlated [87]. When sperm lack energy to survive, their motility can diminish.…”
Section: Effect Of Freezing-thawing On the Functioning Mechanism Of H...mentioning
confidence: 99%